Sosialisasi Dampak Perkembangan Teknologi dan Internet Pada Generasi Z di Banjarmasin - Lestari, Endang; Fatonah, Umi; Syifa, Nadiyatus; Rahmadayanti, Nadya; Azizah, Noor; Faidah, Anna Nur; Sudirwo, Sudirwo (Universitas Negeri Gorontalo, 2024)
The advancement of technology and internet development has changed the way humans communicate, express themselves, do business, and even change the realm of education. Besides its benefits, the internet can have a negative impact like a double-edged knife not only on activities, but also on mental health. Generation z people who were born in 1997-2012 are the generation with the highest level of mental health issues, and currently some are undergraduate students. This service aims to raise awareness of the impact of the internet, and control themselves not to be trapped in dependence on AI and social media on students. Participants in this socialisation were 23 undergraduate students. The method used was socialisation with pre-test and post-test evaluation of students' knowledge. The results of the service showed that the increase in student understanding was moderate, because students already knew theoretically before the socialisation. However, the results of the socialisation effectiveness test showed that it was still less effective, where students already understood the impact from before the socialisation, but not with the use of appropriate AI.